Ukraine Humanitarian Needs and Response Plan 2024 - United Nations Office for the Coordination of Humanitarian Affairs (United Nations, 2024)
This document is consolidated by OCHA on behalf of the Humanitarian Country Team and partners. It provides a shared understanding of the impact of the war on the people of Ukraine, including the most pressing humanitarian needs, the estimated number of people who need assistance. It also outlines the strategy to ensure adequate and timely life-saving and life-sustaining response, and the financial request to make humanitarian operations possible.